2012
DOI: 10.1021/ja210577h
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of Block Copolymers in Supercritical Carbon Dioxide: A Simple Versatile Route to Nanostructured Microparticles

Abstract: We present a one-pot synthesis for well-defined nanostructured polymeric microparticles formed from block copolymers that could easily be adapted to commercial scale. We have utilized reversible addition−fragmentation chain transfer (RAFT) polymerization to prepare block copolymers in a dispersion polymerization in supercritical carbon dioxide, an efficient process which uses no additional solvents and hence is environmentally acceptable. We demonstrate that a wide range of monomer types, including methacrylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
121
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(125 citation statements)
references
References 59 publications
2
121
0
2
Order By: Relevance
“…Previous attempts to fabricate discrete, high aspect ratio polymeric structures has proved difficult without the exploitation of exotic chemical properties such as conductivity, which may give rise to undesirable side effects in vivo . 5-8 …”
mentioning
confidence: 99%
“…Previous attempts to fabricate discrete, high aspect ratio polymeric structures has proved difficult without the exploitation of exotic chemical properties such as conductivity, which may give rise to undesirable side effects in vivo . 5-8 …”
mentioning
confidence: 99%
“…This idea was reinforced by Zhan et al, who synthesised SBAS by RAFT miniemulsion, which also performed comparably to conventional TPEs despite their high Đ (3) and poorly ordered "sea-island" nanostructure. Self-assembly within block copolymer particles synthesised by RAFT scCO2 dispersion was studied by Jennings et al 119 Phase separated structures were observed in a variety of copolymers, despite some relatively low blocking efficiencies (>50%) and high dispersity (Đ = 2). 120 Particles of symmetrical PMMA-b-PBzMA and PMMA-b-PDMAEMA revealed lamellar phase separated morphology, whilst symmetrical PMMA-b-PSt and PMMAb-P4VP showed cylinders and spheres, respectively (Fig.…”
Section: Figure 8: Afm Images Of Films Prepared From Block (A C) Andmentioning
confidence: 99%
“…CO 2 has been exploited as a solvent for polymerisations [7,8], as a foaming agent [1,[9][10][11][12][13], for precipitation/separation [14], particle formation [15,16] and encapsulation [17].…”
Section: Introductionmentioning
confidence: 99%